Revision of the circumtropical glasseye fish Heteropriacanthus cruentatus (Perciformes: Priacanthidae), with resurrection of two species - Fernandez-Silva, Iria; Ho, Hsuan-Ching (Zootaxa, 2017)
The glasseye fish Heteropriacanthus, previously known as a monotypic genus, is now divided into three species based on morphological and genetic features. After examination on the type specimens and literature, herein we resurrect two junior binomens, H. carolinus (Cuvier, 1829) from the Indo-Pacific Ocean and H. fulgens (Lowe, 1838) from the northeastern Atlantic Ocean. Heteropriacanthus cruentatus (Lacepède, 1801) is now considered to be restricted to the Atlantic and southwestern Indian oceans. In light of these observations we discuss the evolutionary history of the genus.